Two Dibenzylbutyrolactol Derivatives and Other Chemical Constituents from Aristolochia peltato-deltoidea - Silva,Ana Paula Freitas da (1999)
The hexane extract from the aerial parts of Aristolochia peltato-deltoidea Hoehne (Aristolochiaceae) afforded two new epimeric lignans of the type dibenzylbutyrolactol, rel-(8R, 8S, 9S)-3,4-dimethoxy-3,4-methylenedioxy-9beta-ethoxy- and rel-(8R, 8S, 9R)-3,4-dimethoxy-3,4-methylenedioxy-9alpha-ethoxy-lignans-8.8,9.O.9, besides a benzofuran neolignan, known as eupomatenoid-7, alpha-tocopherylquinone, beta-sitosterol and stigmasterol. From the chloroform extract were isolated two diastereomeric dibenzylbutyrolactone lignans: rel-(8R, 8R)- and rel-(8R, 8S)-3,4-dimethoxy-3,4-methylenedioxy-9-oxo-lignans-8.8,9.O.9. Chemical composition analysis by GC/MS of the non polar fractions from the hexane extract was also carried out and ten components were identified. The structures of the isolated compounds were elucidated utilizing spectrometric methods.